The Misrepresentation of Petri Dish, as “petri” Dish, in the Scientific Literature - Jaime A. Teixeira da Silva (Studia Historiae Scientiarum, 2023)
The Petri dish is, without a doubt, a very basic, yet important and popular tool in microbiological and other biomedical experiments. It serves primarily as a support or structural platform for placing, growing or testing biological specimens, whether these be microbiological, animal, plant or human.